Effects of high temperatures on rocks - Li, Zhihuan (2018)
Due to competition for usable space, underground construction is an increasingly attractive option. However, the effects of a fire on the integrity and stability of underground rock structures need to be studied further to understand the potential ramification of a fire hazard within an underground rock structure. In this thesis, Brazilian tensile tests are conducted on Bukit Timah Granite specimens after exposure to different heating temperature. The variation of Brazilian tensile strength with respect to heating temperature and cooling rate of the specimens is explored and linked to the color changes of the specimens after heating. A MATLAB script is written to segmentate the specimen from the background of a photo and analyse it for its color values in the CIEL*a*b* color space. A relationship between the heating temperature and the Brazilian tensile strength of the specimens was found, as did a relationship between the color changes and the heating temperature of the specimens. The dynamic compressive strength test was also performed on both heated Bukit Timah Granite and Carrara marble specimens. An increase in heating temperature was found to reduce the dynamic compressive strength of both Carrara marble and Bukit Timah Granite, although the extent of the degradation in dynamic compressive strength is different for both materials. This is most likely due to the difference in the material of the specimens. Stress shadowing was also observed for Carrara marble. The presence of stress shadowing is influenced by the amount of energy used to compress the marble specimen as well as the heating temperature. Following this, microscopic observations of heated Bukit Timah Granite Brazilian tensile test specimens are presented. Comparisons were made between specimens that underwent a combination of heating and mechanical loading. The cumulative microcrack length, microcrack length distribution and microcrack orientation were analysed. The median microcrack length was found to similar despite the different thermal and mechanical loading. The mineralogical texture was also found to influence the length of the microcracks.